Éducation à l'environnement, éducation au développement durable : la double rupture - Patrick Matagne (Éducation et Socialisation)
The purpose of this paper is to identify and characterize a double break, societal and epistemological between environmental education (EE) and education for sustainable development (ESD). This double break, ignored by official instructions of national Education has yet significant educational effects. After presenting in the first part how the French educational system is trying to build a form of continuity between the official EE 1970s and 2000s EDD, double break will be contextualized and analyzed in a second and a third part, to finally open the discussion on the epistemological, social functions and objectives of EE and EED. This text is based on research aimed at clarifying the issues of environment and sustainable development, educational postures induced by the introduction of EE and EED.